Mit grecki - jego modyfikacje, znaczenia i funkcje. Szkic problematyki - Czerwinska, Jadwiga (Collectanea Philologica, 2011)
The subject of the article concerns the issues of ancient Greek myth, its modifications and functions. The starting point for a such formulated problem is the Aristotle’s rules to which a myth is subject. The philosopher links these rules with the theory of tragedy’s poetics, that should be directed by probability. Following the standards, that were in force in Antiquity, a function, which had to be fulfilled by a myth, determined the way of using mythology by Greek dramatists. The modern culture reinterpret a Greek myth. A function, which a myth has to fulfil, as in ancient times, is its basis and determinant. The task of a myth is, first of all, indicated as an universalization of the values, that are inscribed in this myth.